O estudante endiabrado: representação do mito de Dom Juan em espronceda - Pandolfi, Maira Angélica [UNESP] (My University, 2011)
The present study is a reflection on the representation of the literary myth of Dom Juan in the work El estudiante de Salamanca (1836-1840), by Joseph de Espronceda. It highlights the most significant aspects of their recreation donjuanesca, since the classic elements taken from the founding work of Tirso de Molina to Romantic Titan which characterizes Dom Félix de Montemar.

O presente estudo faz uma reflexão sobre a representação do mito literário de Dom Juan na obra El estudiante de Salamanca (1836-1840), de José de Espronceda, destacando os aspectos mais significativos de sua recriação donjuanesca, desde os elementos clássicos retomados da obra fundadora de Tirso de Molina ao titanismo romântico que caracteriza Dom Félix de Montemar.
Keywords: Dom Juan myth; El estudiante de Salamanca (1836-1840); José de Espronceda; Spanish literature of the nineteenth century; Romantic Titan; Mito de Dom Juan; El estudiante de Salamanca (1836-1840); José de Espronceda; Literatura Espanhola do século XIX; Titanismo